2006
DOI: 10.1111/j.1440-1797.2006.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity arteriovenous fistula does not affect pulse oximetry readings

Abstract: An upper extremity AVF alters blood pressure and temperature measurements when compared with the contralateral non-AVF side, but there is no difference in SpO2 provided an adequate signal quality is detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, the long-term survival and quality of life of patients on hemodialysis is dependent on an appropriately placed vascular access; the most reliable long-term method of achieving this being the construction of an arteriovenous fistula (AVF) [15,16]. The resultant arterialization of the vein alters the blood flow distal to the AVF and can theoretically change the skin and axillary temperature [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the long-term survival and quality of life of patients on hemodialysis is dependent on an appropriately placed vascular access; the most reliable long-term method of achieving this being the construction of an arteriovenous fistula (AVF) [15,16]. The resultant arterialization of the vein alters the blood flow distal to the AVF and can theoretically change the skin and axillary temperature [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In comparison, a previous study reported a significant reduction of distal arterial pressure after the creation of an AVF; however, no significant change was observed in O 2 Sat. 26 Also, we found a difference in O 2 Sat of the two sides in the case group (92.9% 6 2.1% vs 95.6% 6 1.4 %; P ¼ .001). Halevy et al 20 described five patients with steal syndrome, in whom O 2 Sat increased from a median of 50% (range, 42%-63%) to 98% (range, 80%-100%) by therapeutic intervention.…”
Section: Discussionmentioning
confidence: 61%